WEED CONTROL AND PRODUCTIVITY OF MAIZE (Zea mays L.) IN MALETE, KWARA STATE OF NIGERIA - Emmanuel, Imoloame Oyamedan (Journal of Agricultural Sciences (Belgrade), 2020)
Field trials were conducted at the Teaching and Research Farm of Kwara State University, Malete, to determine the weed control method that will be more effective in controlling weeds and give higher grain yield and cash returns in the production of maize. The experiment consisted of 9 treatments viz: primextra (metolachlor plus atrazine) +2,4 – D at 1.5 + 1.5 kg a.i.ha-1, primextra +2,4-D at 2.0 + 2.0 kg a.i.ha-1, primextra + 2, 4 –D at 2.5+2.5 kg ha-1, primextra + nicosulfuron at 1.5 + 0.03 kg a.i.ha-1, primextra + nicosulfuron at 2.0 + 0.05kg a.i.ha-1, primextra + niconsulfuron at 2.5+0.07kg a.i.ha-1 , primextra at 1.5 + one Supplementary Hoe Weeding (SHW) at 6 Weeks After Sowing (WAS), two hand weeding at 3 and 6 Weeks After Sowing (WAS) and a weedy check. These treatments were laid out in randomized complete block design (RCBD) with three replicates. Data collected were subjected to analysis of variance using Statistical Analysis Software (SAS) package, after which means were separated using Duncan’s Multiple Range Test (DMRT). Results showed that treatment combinations of primextra + oneSHW at 6 WAS, two hoe weeding at 3 and 6 WAS, primextra +2, 4-D at 2.0 + 2.0 kg a.i.ha-1 and primextra + nicosulfuron at 2.0+0.05 kg a.i.ha-1 gave effective weed control, higher grain yield and cash returns. They are therefore recommended for application in rotation by farmers in Malete.